2022
DOI: 10.37284/eajbe.5.1.522
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Green Recruitment and Selection on Sustainability of Selected Tea Factories in Kericho Highlands Region, Kenya

Abstract: The focus of this study was to assess the influence of green recruitment and selection on the sustainability of selected tea factories in Kericho Highlands region, Kenya. The study was anchored on human capital theory. It adopted a correlational research design, with a targeted population of 915 respondents drawn from tea factories in the Kericho highlands region. A sample size of 278 respondents was determined scientifically using the Yamane taro formula. Primary data was collected using a structured question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This suggests that the employment of individuals who exhibit the pro-environmental attitude and awareness may improve their job performance The current findings are consistent with the findings of previous research (Kiplangat et al, 2022;Liu et al, 2021). The third hypothesis was formulated to examine the effect of the Green Training and Development on employees' job performance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This suggests that the employment of individuals who exhibit the pro-environmental attitude and awareness may improve their job performance The current findings are consistent with the findings of previous research (Kiplangat et al, 2022;Liu et al, 2021). The third hypothesis was formulated to examine the effect of the Green Training and Development on employees' job performance.…”
Section: Discussionsupporting
confidence: 87%
“…In the financial industry, GRS may be of assistance to banks in their efforts to recruit and retain staff who are devoted to environmental sustainability, which can have a positive impact on the overall performance of the bank (Zhang, Wang, Zhong, Yang & Siddik, 2022). For instance, banks may enhance their environmental performance and fulfill the growing demand for the environmentally responsible banking procedures if they hire people who are aware about environmental concerns and devoted to sustainability (Kiplangat, Sang & Kingori, 2022). Green Training & Development (GTD) and Green Compensation Management (GCM) are two ways that may help to promoting the environmental sustainability and strengthening the performance of banks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, business entities project themselves as green firms to attract talents with green skills and those concerned about the sustainability of the environment. At the same time, prospective employees focus on orienting themselves to the international standard of green culture as they believe it will enhance their job market (Kiplangat, Sang, & Kingori, 2022). Saeed et al (2019) assert that in the job description, the firms should clearly state what they expect from the employees regarding green practices.…”
Section: Green Recruitment and Selectionmentioning
confidence: 99%
“…Many past studies have concluded that different GHRM practices individually and collectively affect environmental performance (Jamal et al, 2021). GHRM practices, including "green recruitment, green training, and green rewards, " positively affect the environmental performance of firms and give them a competitive edge (Singh & El-Kassar, 2019;Khan et al, 2021;Kiplangat, Sang, & Kingori, 2022).…”
Section: Green Reward Systemmentioning
confidence: 99%